Revitalizing Ritual Performances for Environmental Conservation and Climate Change Adaptation: A Case Study of Ecotourism in Khaw Nu M’cung National Park, Myanmar - Bawi, Salai Vanni (Forest and Society, 2025)
Environmental conservation is vital for sustaining biodiversity, ensuring ecosystem services, and mitigating climate change. Despite its importance, a theoretical gap exists in integrating indigenous knowledge with contemporary conservation strategies. Indigenous knowledge, which deeply coexisted with cultural practices, has been marginalized due to colonial histories and religious development. This marginalization neglects valuable ecological insights embedded in traditional rituals and practices. However, ecotourism presents a promising avenue for bridging this gap by leveraging the symbiotic relationship between indigenous communities and their natural environment. The ecotourism centered on indigenous practices fosters environmental stewardship and empowers local communities economically and culturally. Ecotourism can enhance conservation efforts while promoting sustainable tourism activities that highlight traditional ecological knowledge while preserving cultural heritage. In the context of Khaw Nu M’cung National Park in Myanmar, incorporating Chin indigenous rituals and traditional activities into ecotourism initiatives offers a holistic approach to environmental conservation. The touristic performance can guide sustainable resource management and biodiversity preservation. This study proposes a new dynamic of ecological conservation, emphasizing the revival and integration of indigenous rituals and traditional knowledge. Doing so aims to create a sustainable model that respects cultural heritage while addressing contemporary conservation challenges, ensuring the harmonious coexistence of nature and indigenous communities.